TRADE SPECIALIZATION AND COMPETITIVENESS OF THE INDIAN ONION MARKET IN RELATION TO BIMSTEC MEMBER NATIONS - M. M. Hossain; S. K. Sen; M. S. Islam; M. K. Chakma; M. Sh. Hossain (مجلة الأنبار للعلوم الزراعية)
This study examined the extent of competitiveness in onion trade specialization and the comparative advantage between India and other BIMSTEC member nations from 2005 to 2021. It used secondary data from the OEC database and factored in the repeated pandemics and trade frictions. The findings indicate that India exhibited greater competitiveness in the onion market within the BIMSTEC region. The study concluded that India has a notable advantage over other BIMSTEC member nations in onion production and export. The study employed the Revealed Comparative Advantage Index (RCA), including the Balassa, Lafay, and the Grubel-Lloyd Indices, to determine the level of intra-industry trade and the trade balance index (TBI) to determine competitiveness level. India benefits from a significant edge in onion exports due to its high production capacity and strategic geographical location near major importing nations. The study recommended that India expand its market globally since more than half of onion exports are transacted amongst BIMSTEC nations, especially Bangladesh and Bhutan, the world’s largest producer of onions. India must rethink its strategies to become the top commodity exporter globally